Atlas of Bone Pathology - Wei, Shi. (Atlas of Anatomic Pathology,, 2013)
Bone is a living tissue prone to develop a diverse array of inflammatory, metabolic, genetic, reactive, circulatory and neoplastic abnormalities.  The Atlas of Bone Pathology describes and selectively illustrates the normal and pathologic conditions that afflict human bone, focusing heavily on tumor and tumor-like conditions of bone and their non-neoplastic mimics.  Supplemented with radiographic and special study images, this extraordinary collection of high quality digital images aid in continuing efforts to recognize, understand, and accurately interpret the light microscopic findings in bone specimens. Authored by nationally and internationally recognized pathologists, The Atlas of Bone Pathology is a concise and useful resource for both novice and seasoned pathologists alike.